2022
DOI: 10.1108/jamr-05-2021-0182
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance determinants of asset quality in an emerging economy: evidence from Indian banks

Abstract: PurposeThis paper aims to identify specific corporate governance determinants of asset quality in the Indian banking system and suggest a future course of action for research in the Indian banking industry. The results will guide other developing nations to handle poor asset quality in banks. Nations with economic interest in India can take cognisance from the results.Design/methodology/approachThe authors identify the determinants of asset quality for the Indian banks using novel data from 2010 to 2019 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…Either sector should utilize the other sectors’ strengths to improvise their own corporate governance in order to improve asset quality. The result of each determinant has been discussed below based on the findings of (Gupta and Sharma, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Either sector should utilize the other sectors’ strengths to improvise their own corporate governance in order to improve asset quality. The result of each determinant has been discussed below based on the findings of (Gupta and Sharma, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the existing literature identifies seven corporate governance determinants (Gupta and Sharma, 2022) that this article uses in its empirical analysis. They are board size, gender diversity, number of board meetings, audit committee meetings, CEO duality, ownership concentration and board independence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate Governance memiliki peran yang sangat penting untuk menjaga kelangsungan bisnis dan meningkatkan kinerja keuangan perusahaan (Abdoush, 2022). Corporate Governance telah menjadi topik yang semakin penting dalam industri penerbangan karena industri ini memiliki risiko yang sangat tinggi dan ketatnya peraturan yang diterapkan oleh pemerintah (Gupta & Sharma, 2022). Dalam industri penerbangan, Corporate Governance adalah mekanisme penting untuk memastikan bahwa perusahaan dikelola dengan baik dan menjaga kepentingan seluruh stakeholder.…”
Section: Pendahuluanunclassified
“…Empirical evidence reveal that corporate governance and firm performance are inconclusive, and these studies have shown mixed results (Alabdullah 2018;Buallay et al 2017). From a positive perspective, studies found corporate governance characteristics to significantly impact the performance of firms (Ahmed and Hamdan 2015;Gupta and Sharma 2022). A research study by Buallay et al (2017) in Saudi Arabia using 171 listed firms demonstrated that more robust corporate governance systems of a firm significantly improve its performance.…”
Section: Introductionmentioning
confidence: 99%